Architecture from the Ground Up: Designing and Delivering Social Value in Southern India. (2nd July 2020) - Lad, Jateen
Abstract: Architect Jateen Lad details the socially empowering design and project delivery strategies for the Sharanam Centre for Rural Development in southern India and their catalytic effect on local communities. The trust and dialogue between the architect, NGO client and workers was crucial in the development of technical skills and improved livelihoods that continue to help the communities thrive.